USING LOCAL TASTES IN ELT CLASSROOMS TO PROMOTE LEARNERSâ NATIONALISM - Siswoyo, Siswoyo (STKIP Muhammadiyah Pringsewu, 2017)
AbstractÂ This article aims at exploring the use of local taste in English Language Teaching (ELT) classroom especially for the elementary school students. Teaching English since elementary school has lots of advantages for the language learners. The students will be native like if they learn English as early as possible. Their pronunciation will be more native like rather than the adult because they have not exceeded the critical period. By using the local taste in teaching English, the students will be able to promote their local taste in international world. Promoting local taste towards international world is one of the efforts to increase the studentsâ nationalisms.Â Keywords: local taste, English language teaching, nationalism